Javanese ethnopuitics variant: A study on Indonesian literary works - Putera Manuaba, Ida Bagus; Setijowati, Adi (Opción, 1970)
Indonesian literary works has been produced by East Javanese authors. However, the existence of this literary work is not widely known by both national and international readers. This study aims to reveal the existence of literary works by East Javanese authors, especially discovering the ethnopoetics. This study used a textual qualitative method, with literature sociological perspective. Literary textual data were studied analytical-interpretatively by deep reading, recording, and interpreting. The finding of this study showed that Indonesian literature ethnopoetics as a characteristic of East Javanese authors was colored with themes and aesthetics typical of East Java.